A bacterial cytidine deaminase toxin enables CRISPR-free mitochondrial base editing - Mok, Beverly Y.; de Moraes, Marcos H.; Zeng, Jun; Bosch, Dustin E.; Kotrys, Anna V.; Raguram, Aditya; Hsu, FoSheng; Radey, Matthew C.; Peterson, S. Brook; Mootha, Vamsi K.; Mougous, Joseph D.; Liu, David R. (Nature (London), 2020)
Bacterial toxins represent a vast reservoir of biochemical diversity that can be repurposed for biomedical applications. Such proteins include a group of predicted interbacterial toxins of the deaminase superfamily, members of which have found application in gene-editing techniques 1 , 2 . Because previously described cytidine deaminases operate on single-stranded nucleic acids 3 , their use in base editing requires the unwinding of double-stranded DNA (dsDNA)—for example by a CRISPR–Cas9 system. Base editing within mitochondrial DNA (mtDNA), however, has thus far been hindered by challenges associated with the delivery of guide RNA into the mitochondria 4 . As a consequence, manipulation of mtDNA to date has been limited to the targeted destruction of the mitochondrial genome by designer nucleases 9 , 10 .Here we describe an interbacterial toxin, which we name DddA, that catalyses the deamination of cytidines within dsDNA. We engineered split-DddA halves that are non-toxic and inactive until brought together on target DNA by adjacently bound programmable DNA-binding proteins. Fusions of the split-DddA halves, transcription activator-like effector array proteins, and a uracil glycosylase inhibitor resulted in RNA-free DddA-derived cytosine base editors (DdCBEs) that catalyse C•G-to-T•A conversions in human mtDNA with high target specificity and product purity. We used DdCBEs to model a disease-associated mtDNA mutation in human cells, resulting in changes in respiration rates and oxidative phosphorylation. CRISPR-free DdCBEs enable the precise manipulation of mtDNA, rather than the elimination of mtDNA copies that results from its cleavage by targeted nucleases, with broad implications for the study and potential treatment of mitochondrial disorders. An interbacterial toxin that catalyses the deamination of cytidines within double-stranded DNA forms part of a CRISPR-free, RNA-free base editing system that enables manipulation of human mitochondrial DNA.